An analysis of underemployment among young graduates: The case of a higher education institution in South Africa - Daniel Meyer; Precious Mncayi (Economies, 2021)
Labour markets have undergone vast transformations over the last few years. There are arguments that employment and unemployment measures have not been adequate in understanding the complexities of labour markets. Research on labour underutilisation has focused on one side of the spectrum, which is just about the scarcity of jobs. However, there is more to the labour market than just scarcity of jobs, and many researchers believe unemployment is not a complete measurement of unused labour capacity, which is why this study aimed to investigate the existence of underemployment from the perceptions of young graduates themselves. In this regard, the definition of young people entailed those younger than 35 years as officially defined in South Africa. The study employed a primary data method of data collection in which an online survey was used to collect the necessary data from the alumni database of a South African university. The study used binary logistic regression to determine factors that contributed to or influenced underemployment status. The main findings indicated that underemployment was rife according to age, where younger graduates (20–29 years) were more likely to be underemployed compared to their more mature counterparts; that is, those in the 30-34 age category, with non-White graduates most likely to encounter underemployment compared to their counterparts. This study resulted in important findings that carry significant policy implications and recommendations that may be crucial in correcting the current employment mismatches in the South African graduate labour market.
Keywords: 330; graduate underemployment; South Africa; university graduates; youth